A novel scheme for weld microstructure control using cryogenic cooling - Muhammed Olawale Hakeem, Amuda; Mridha, Shahjahan (Trans Tech Publications, 2011)
In this work, the preliminary result on the effect of cryogenic cooling on grain growth in weld is reported. Ferritic stainless steel weld produced under TIG torch in argon environment is cooled in liquid nitrogen. The weld structure is characterized using LOM, SEM and EDX spectroscopy. The results suggest that cryogenic cooling reduced the weld width within 2% to 5% and HAZ to 39% relative to those cooled in normal condition. This ensures that the area of the base metal affected and exposed to the weld thermal cycle is reduced and hence probably generates less metallurgical distortion. The cryogenic cooling also generated 14% to 36% grain refinement compared to welds cooled in normal condition.